AL-‘ASHER SCHOOL: THE PHILOSOPHICAL OF K.H. AHMAD DAHLAN’S CHARACTER EDUCATION - Khoirudin, Azaki; Anshori, Ari (Muhammadiyah University Press, 2018)
This article is a philosophical reflection of KH. Ahmad Dahlan educational practice. Based on the historical fact that KH. Ahmad Dahlan undertook the character education contained in Surah Al-'Ashr to his students for 7-9 months. This educational practice is manifested in the form of ?Pengajian Wal-'Ashri? for young women and ?Wal-'Ashri Cadre School? for male youth. This makes the spirit and ethos of al-'Ashr embedded in young men and women, thus creating a